Pergeseran Bahasa di Area Ekowisata Multiligual Desa Loid Kabupaten Halmahera Selatan - Samad, Sartika; Ahmad, Idrus; Umabaihi, Riski; Galela, Sarmina B. (Jurnal Ilmiah Wahana Pendidikan, 2023)
Language shift in general is a phenomenon, where the words and phrases of one language are replaced by those of another language. The causes are the attitude of language users who consider other languages ​​to be more trendy and easier to use, language loyalty, and the continuity of mother-tongue transfer between generations. Language shifts are also caused by schools. School is a factor causing the shift in students' mother tongue because schools usually teach foreign languages ​​to children. This is also sometimes the cause of the shift in the position of regional languages. One of the symptoms of language shift which is the object of this research is East Macanese (BMT) to Ternate Malay (BMTe). The aim of this research is to analyze and describe the manifestation of the shift from BMT to BMTe in several areas, including: time, family, maritime, agricultural and general. This research uses descriptive research methods according to contextual problems obtained through initial observations and has been planned in the research proposal. The location of this research is Loid Village, South Halmahera Regency, North Maluku Province. This location was chosen because it is a concentration of 5 regional languages ​​and Ternate Malay which often switches codes and mixes codes.